Teacher’s Subject-Professional Position: Nature, Structure - Мария Шиманчик (Людинознавчі студії: Серія Педагогіка, 2017)
The article deals with the author’s approach to the definition of the nature of the teacher’s subject-professional position as a person’s integrative qualitative characteristic. The structure of the teacher’s subject-professional position is grounded, which includes the unity of three interrelated components: value-motivational, meaningful-active and personal components. The nature of each component, its functions and content are discussed.